MANAJEMEN PENGELOLAAN PIUTANG PADA PT. FEDERAL INTERNASIONAL FINANCE (FIF) DI KABUPATEN BOALEMO - Sukrianto Sukrianto; Fibriyanti S. Lakoro (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
The purpose of this study was to describe the management of accounts receivable management at PT. Federal International Finance (FIF) in Boalemo Regency. The type of research used is phenomenological research with a qualitative approach. The data sources used are primary data sources and secondary data sources. The data analysis method used is the Miles and Huberman model data analysis technique with the stages of data reduction, data presentation and drawing conclusions or data verification. The results of this study indicate that the management of receivables at PT. Federal International Finance (FIF) of Boalemo Regency through the credit department or department must carry out a detailed examination either administratively or in accordance with the 5 C terms with the aim of knowing the customer's background. The return system must be adjusted to the policies of PT. Federal International Finance (FIF) in minimizing bad loans that will occur. So that the ability of consumers to repay receivables or credit can be according to the specified time and not past due